Kidney and combined kidney and pancreas transplantation may be under-utilized in cystic fibrosis - Woywodt, Alexander; Dhanda, Raman; van Dellen, David; So, Beng; Bright-Thomas, Rowland J. (Frontiers in Transplantation, 2022)
Cystic fibrosis (CF) is a multisystem disorder and represents the most common inherited condition leading to death in Western countries. Previous reports of chronic kidney disease (CKD) in CF focus on cases post lung, or other solid organ, transplantation but CKD in CF patients pre transplantation is increasingly recognised as a challenging complication of CF. CKD can evolve as a sequel to acute kidney injury for example after prolonged treatment with aminoglycoside antibiotics during episodes of infection. Nephrolithiasis, diabetic nephropathy and a variety of glomerular lesions, such as amyloidosis and Immunoglobulin A nephropathy are also seen. Muscle depletion is common in CF, hence creatinine-based estimates of kidney function may underestimate the degree of renal impairment and lead to delayed diagnosis and management. Improved treatment options for CF patients have resulted in a sustained increase in life expectancy with increasing numbers of CF patients with CKD approaching end-stage renal failure prior to consideration of lung transplantation. We believe that kidney or combined kidney-pancreas transplantation are under-utilised in this population. We provide a brief primer on the landscape of CF and CKD and discuss transplant options. Suitable patients with CF and advanced CKD should be formally assessed for kidney or kidney-pancreas transplantation.